The Impact of Digital Transformation on Labor Productivity in the Service Sector - Zulhan Awaludin; Chengzhi Qiao Xie (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digital transformation has reshaped the service sector by integrating advanced technologies into business processes. This study aims to analyze the impact of digital transformation on labor productivity in the service sector across different economic contexts. The research applies a qualitative systematic literature review approach using recent empirical studies published between 2021 and 2025. The findings indicate that digital transformation significantly improves labor productivity through process automation, data-driven decision making, and enhanced communication efficiency. Studies show that productivity gains are more pronounced in high-income economies due to better technological infrastructure and human capital readiness. However, challenges such as digital inequality, workforce skill gaps, and organizational adaptation remain critical barriers. The study also finds that digital transformation shifts labor demand toward high-skilled workers, thereby influencing employment structures. This research contributes to the literature by synthesizing cross-country evidence and highlighting the mechanisms linking digital transformation and productivity. The findings provide practical implications for policymakers and firms to design strategies that maximize productivity gains while addressing structural challenges in the service sector.